2011
DOI: 10.1152/ajpgi.00168.2011
|View full text |Cite
|
Sign up to set email alerts
|

Urine sugars for in vivo gut permeability: validation and comparisons in irritable bowel syndrome-diarrhea and controls

Abstract: Mucosal barrier dysfunction contributes to gastrointestinal diseases. Our aims were to validate urine sugar excretion as an in vivo test of small bowel (SB) and colonic permeability and to compare permeability in patients with irritable bowel syndrome-diarrhea (IBS-D) to positive and negative controls. Oral lactulose (L) and mannitol (M) were administered with (99m)Tc-oral solution, (111)In-oral delayed-release capsule, or directly into the ascending colon (only in healthy controls). We compared L and M excret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
172
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(183 citation statements)
references
References 34 publications
10
172
0
1
Order By: Relevance
“…Apart from this last line of defence, the mucus layer covering the intestinal mucosa as well as the gut microbiota and products from the immune system (such as defensins and secreted antibodies) have important roles in maintaining gut integrity. 135 Between 12% and 50% of patients with IBS have been reported to have altered intestinal permeability in research studies 136 using various methods to reflect gut permeability at different parts of the gastrointestinal tract, [137][138][139] and both postinfectious IBS as well as nonselected groups of patients with IBS have been investigated. An acute bacterial infection results in a transient increase in intestinal permeability.…”
Section: Barrier Functionmentioning
confidence: 99%
“…Apart from this last line of defence, the mucus layer covering the intestinal mucosa as well as the gut microbiota and products from the immune system (such as defensins and secreted antibodies) have important roles in maintaining gut integrity. 135 Between 12% and 50% of patients with IBS have been reported to have altered intestinal permeability in research studies 136 using various methods to reflect gut permeability at different parts of the gastrointestinal tract, [137][138][139] and both postinfectious IBS as well as nonselected groups of patients with IBS have been investigated. An acute bacterial infection results in a transient increase in intestinal permeability.…”
Section: Barrier Functionmentioning
confidence: 99%
“…There may be interfering substances that could affect the assayed levels of sugars, particularly food derived substances. Gut transit of liquids can also be a problem as a liquid bolus can reach the colon within 2 hours, meaning that collection of urine 5 hours post sugar dosing may reflect colonic absorption [Rao et al 2011].…”
Section: Assessing Intestinal Permeabilitymentioning
confidence: 99%
“…When actin contracts, it leads to increased permeability to electrolytes and small molecules [105] . In the context of inflammatory bowel syndrome (IBS), some studies have shown that the intestinal barrier is compromised, and decreased expression and differential distribution of tight-junction proteins are observed [106][107][108][109][110] . The nature of the luminal or mucosal factors that affect the function of tight junction proteins is still unclear.…”
Section: Gut Permeability: An Unclear Connection Between Altered Gut mentioning
confidence: 99%